Combined use of creatinine and cystatin C improves the detection of renal dysfunction in children undergoing home parenteral nutrition. Issue 1 (22nd April 2021) - Matrat, Lucie; Ruiz, Mathias; Ecochard‐Dugelay, Emmanuelle; Loras‐Duclaux, Irène; Marotte, Stéphanie; Heissat, Sophie; Poinsot, Pierre; Sellier‐Leclerc, Anne‐Laure; Bacchetta, Justine; Dubourg, Laurence; Peretti, Noël
Abstract: Background: Renal dysfunction can complicate home parenteral nutrition (HPN). The aims were, in the context of pediatric HPN, to assess renal function using the measured glomerular filtration rate (mGFR), determine the most accurate formula(s) to estimate GFR, and identify possible underlying mechanisms of renal impairment. Methods: A retrospective study was performed in 2 centers. Patients receiving HPN and aged 2–16 years without medical history of nephropathy were included. GFR was measured using iohexol clearance. Estimated GFR (eGFR) was calculated using creatinine, cystatin C–based, and combined (eGFRcr+cyst ) Schwartz formulas. Results: A total of 36 patients (18 females) were included; they received HPN for 8 (2–16) years. The primary digestive disease was short‐bowel syndrome for 16 (44%) patients, gastrointestinal motility disorder for 10 (28%), or congenital diarrhea for 10 (28%). The median (range) mGFR was 99 (33–136) ml/min/1.73 m 2 ; 9 (25%) patients had mildly decreased mGFR (<90 and ≥60 ml/min/1.73 m 2 ), and 2 (6%) had mildly to severely decreased mGFR (<60 ml/min/1.73 m 2 ). The eGFRcr+cyst formula was the most accurate and precise to estimate GFR. A significant negative correlation between mGFR and PN duration was found for patients receiving PN for 6–7/7 days ( P = .008). Activation of the renin‐angiotensin system was identified in 15 of 36 (42%) patients. Conclusion: Renal dysfunction was frequent and correlated with the duration of PN only for patients with the most severe intestinal failure. The use of eGFRcr+cyst improves its detection in these patients. Chronic dehydration may be an underlying mechanism.